2020
DOI: 10.1007/s00268-020-05589-w
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Pancreatic Stone Protein is Unaffected by Trauma and Subsequent Surgery in Burn Patients

Abstract: Background Altered levels of pro-inflammatory markers secondary to trauma or surgery present a major problem to physicians in being prone to interfere with the clinical identification of infectious events. Methods Patients admitted to Zurich Burn Center between May 2015 and October 2018 with burns C10% total body surface area (TBSA) and without infection. Longitudinal analysis of the time course of PSP and routine inflammatory biomarkers [procalcitonin (PCT), C-reactive protein (CRP) and white blood cells (WBC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
(50 reference statements)
1
4
0
Order By: Relevance
“…Besides this unaffectedness of the biomarker course by the type of sepsis definition, PSP revealed higher absolute values for septic patients at several time points after the first 48 h. Despite some days lacking significance between septic and non-septic patients, PSP was the only marker to demonstrate a highly significant interaction between time and group (sepsis versus no sepsis), connoting that septic patients exhibit a crucial increase in PSP serum levels over time as opposed to non-septic patients. These findings have recently been published by our group in detail using the Sepsis-3 definition [ 14 , 18 , 26 ]. However, results from longitudinal studies on sepsis biomarkers have to be interpreted with caution as the time-dependency of the infectious/septic event is inherently not accounted for.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Besides this unaffectedness of the biomarker course by the type of sepsis definition, PSP revealed higher absolute values for septic patients at several time points after the first 48 h. Despite some days lacking significance between septic and non-septic patients, PSP was the only marker to demonstrate a highly significant interaction between time and group (sepsis versus no sepsis), connoting that septic patients exhibit a crucial increase in PSP serum levels over time as opposed to non-septic patients. These findings have recently been published by our group in detail using the Sepsis-3 definition [ 14 , 18 , 26 ]. However, results from longitudinal studies on sepsis biomarkers have to be interpreted with caution as the time-dependency of the infectious/septic event is inherently not accounted for.…”
Section: Discussionsupporting
confidence: 63%
“…Only Sepsis-1 includes the white blood cell count (WBC), while Sepsis ABA 2007 and Sepsis-3 include the thrombocyte count as a “pro-inflammatory correlate”. Additionally, these canonical biomarkers often fail to uncover infectious events at an incipient stage of the disease as their alterations are prone to interfere with further stimuli such as trauma severity (i.e., total burned surface area (TBSA) in burns), repetitive surgical interventions, and concomitant conditions like inhalation injury [ 12 , 13 , 14 ]. Recently, evidence on the usefulness of pancreatic stone protein (PSP) as an accurate diagnostic and prognostic marker in critically ill patients is accumulating [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, this might simply have highlighted the possible advantage of PSP over PCT and CRP in particular situations characterized by severe non-infectious systemic inflammatory states. Two studies including patients post-burn trauma recently confirmed this observation [ 29 , 30 ]. Interestingly, PSP levels rose up to 72 h before the clinical diagnosis of infection, confirming its potential role as an early biomarker of infection.…”
Section: Discussionmentioning
confidence: 66%
“…After cardiac surgery, PSP performed better than CRP and white blood cell count for the diagnosis of infection [43]. Klein et al [49] showed that in a cohort of burn patients admitted to the ICU without sepsis, the serum levels of PSP remained unchanged over time not only after the initial burn injury but also after secondary debridement procedures in contrast to CRP and PCT both of which significantly increased after inflammatory and/or surgical insults, suggesting that PSP might be a more robust biomarker of sepsis in this particular setting. In another cohort of burn patients admitted to the ICU, PSP demonstrated a 3.3-5.5-fold increase for up to 72 h before the diagnosis of sepsis [50] and among those with inhalation injury and ARDS, PSP was the strongest marker to identify sepsis when compared to CRP and PCT both by its higher values and steeper increase over time [51].…”
Section: Psp Performance For the Diagnosis Of Infection And Sepsismentioning
confidence: 99%